Potensi Terapeutik Ekstrak Daun Clitoria ternatea (Kembang Telang): Aktivitas Farmakologi, Profil Fitokimia, dan Keamanan - Marpaung, Abdullah Muzi (Jurnal Agroteknologi, 2025)
Clitoria ternatea (butterfly pea) leaves constitute a unique phytochemical system within the species, rich in non-anthocyanin compounds that exhibit diverse pharmacological activities. While the flower has been extensively studied for its anthocyanin pigments, the leaf demonstrates broader and more sustained bioactivity due to its abundance of flavonoids, phenolic acids, triterpenoids, alkaloids, and cyclotides. This review critically examines the phytochemical composition, pharmacological mechanisms, and safety profile of C. ternatea leaves based on contemporary experimental and analytical evidence. Quantitative analyses reveal that leaf extracts possess higher total phenolic and flavonoid contents than other plant parts, correlating with strong antioxidant and antidiabetic capacities. Major bioactives such as taraxerol, vasicine-type alkaloids, and the cystine-knot cyclotide Cter M contribute synergistically to antioxidant defense, anti-inflammatory modulation, and glucose regulation. Experimental findings also indicate analgesic, antimicrobial, and neuroprotective activities mediated through inhibition of COX-2, α-glucosidase, and acetylcholinesterase, along with enhancement of Nrf2-dependent antioxidant pathways. Toxicological studies suggest a wide safety margin, with oral LD₅₀ values exceeding 2000 mg/kg and no significant histopathological alterations in vital organs. The absence of major adverse effects supports the short-term safety of leaf extracts, although data on chronic and reproductive toxicity remain insufficient. Overall, available evidence identifies C. ternatea leaves as a promising source of multifunctional bioactive compounds with considerable potential for future development in phytopharmaceutical and nutraceutical applications.Keywords: health benefits, medicinal plants, pharmacological activities, phytochemical composition